Bronchoscopic instillation of amphotericin B is a safe and effective measure to treat pulmonary mycosis - Yang, Lei; Yang, Changqing; Wan, Nansheng; Xie, Wei; Tian, Yu; Xiao, Yangbao; Luo, Li; Chen, Enguo; Zhang, Jisong; Wang, Xiaoping; Xu, Li; Wang, Xingguang; et al. (Frontiers in Pharmacology, 2023)
Background and objectives: In recent years, there has been a significant increase in the prevalence of pulmonary mycosis disease, and its mortality has increased. There are very few studies on treating pulmonary mycosis infections with bronchoscopic instillation of amphotericin B. This study investigated the clinical efficacy and safety of bronchoscopic instillation of amphotericin B for treating pulmonary mycosis infections. Methods: This was a multi-centre, retrospective clinical study of 80 patients with pulmonary mycosis infections who were treated with bronchoscopic instillation of amphotericin B. The efficacy and safety of this treatment were evaluated. Results: Eighty patients were included (51 males; mean (standard deviation [SD]) age, 46 [15.9] years). The most common underlying cause was haematological malignancy (73.75%). The mean number of bronchoscopic instillations of amphotericin B was 2.4 (SD 1.5). In terms of treatment success, 58 (72.5%) patients achieved complete or partial changes on imaging after treatment. A total of 62 (77.5%) patients achieved complete or partial changes on imaging and/or local limitation of the mycosis infection. Seventy-six (95%) patients achieved complete or partial changes on imaging and/or local limitation of mycosis infection and/or an immunotherapy time window. The efficacy rates for treatment of Aspergillus and Mucor infections in terms of the three treatment success criteria described above were 73.81% vs. 63.64%, 80.95% vs. 72.73%, and 92.86% vs. 90.91%, respectively. Conclusion: Bronchoscopic instillation of amphotericin B is safe and effective for treatment of pulmonary mycosis infections.